282. Adherence to Acute Otitis Media guidelines in Pediatricians' Offices, Urgent Care Centers, and a Pediatric Emergency Department. (26th November 2018) - Islam, Shamim; Hassinger, Amanda
Abstract: Background: Acute otitis media (AOM) is a common diagnosis in outpatient pediatrics that often results in antibiotic prescriptions. In 2013, revised clinical practice guidelines for AOM by the American Academy of Pediatrics (AAP) recommended reserving antibiotics and a watchful waiting (WW) approach in most scenarios; amoxicillin ±clavulanate as first-line agents if treating; and courses of >7 days to be clearly indicated only in severe cases in those ≤2 years old. Adherence to AOM guidelines amongst pediatric providers, especially in nonacademic outpatient settings, has not been well characterized. Methods: In a large community-based sepsis point prevalence study, diagnosis, antibiotic prescription, and other data were collected from all patients aged 0 to 18 years seen on September 5, 2016, December 5, 2016, March 6, 2017, and June 5, 2017, in the Emergency Department (ED) of the Women and Children's Hospital of Buffalo, 11 primary pediatric (PMD) offices, and 2 private urgent care centers (UCC) in Buffalo, NY. For this secondary analysis, all children with a provider diagnosis of acute otitis media (AOM) were identified. Adherence to AAP AOM guidelines were analyzed and compared relative to clinical care setting. Results: Of 2, 062 sick visits, 6% (121) were diagnosed with AOM, and in 82% of these antibiotics were prescribed: 91% (39/43) in ED; 70% (21/30) in UCC; 83% (40/48) in PMD, P = 0.071. When prescribed, 69% of antibiotics were first-line agents. In UCC and PMD, oral third-generation cephalosporins were the most common non-first-line agents, followed by azithromycin (20% and 8% of all antibiotic prescribed cases respectively). Ninety percent of antibiotic courses were ≥7 days. There were no differences in prescribing practices between outpatient settings Conclusion: A recent study found that WW is clinically appropriate in >50% of pediatric AOM and overall cost-effective. However, in our analysis, antibiotics are still being prescribed in four out of five cases. Non-first-line agents, which are excessively broad and/or suboptimal in targeting the main pathogens for pediatric AOM, are given in over a quarter of prescriptions. Increasing awareness and adherence to AOM guidelines, in various outpatient settings, should be a major target of pediatric antibiotic stewardship efforts. Disclosures: All authors: No reported disclosures.